INTERPROFESSIONAL APPROACHES TO SYMPTOMS OF DEMENTIA - Tamatha Arms; Noell Rowan; Ana Eusse (European Scientific Journal, ESJ, 2014)
Alzheimer’s disease, the most common form of dementia, is one of the leading causes of death in the United States. Interdisciplinary teams of professionals are called upon to provide a variety of treatment modalities using evidence-based practice. Nursing and social work team members are frequently called upon as professional team members on the front line of service delivery for persons with dementia. This study uses audio and audiovisual simulation experiences of persons with dementia in the preparation of nursing and social work students. Measures utilized included The Dementia Attitudes Scale (DAS) and the Kiersma-Chen Empathy Scale (KCES). Results demonstrated significant change in attitudes and level of empathy toward persons with dementia.